Antifungal effects of eugenol on Candida albicans adherence to denture polymers - Zanul Abidin, Zubaidah; Mohd Salleh, Nosizana; Himratul-Aznita, Wan Harun; Ahmad, Siti Fauzza; Lim, Ghee Seong; Raja Mohd, Noorhayati; Dziaruddin, Nabihah (PeerJ, 2023)
Background The study’s objective is to assess the adherence of C. albicans in different types of denture polymers and the effectiveness of eugenol and commercialized denture cleansers in the removal of C. albicans. Three types of denture base polymers (Lucitone® 199 (High-Impact PMMA), Impact® (conventional PMMA) and Eclipse® (UDMA)) and two hard denture reline materials (Kooliner® and Tokuyama® Rebase II Fast) were used in this study. Methods Three hundred samples were prepared (6 × 2 mm disc shape) and divided into five groups of denture polymers (n = 60) and further subjected into five treatment groups (Polident®, Steradent, distilled water, eugenol 5-minutes, and eugenol 10-min). Three samples were extracted from each treatment group for baseline data (n = 12). Baseline data were used to calculate the initial number of C. albicans adherence. A 0.5 ml immersion solution from each specimen was cultured on YPD agar and incubated for 48 h at 37 °C. Visible colonies were counted using a colony counter machine (ROCKER Galaxy 230). Results The result showed that the denture base polymer significantly affected the initial adherence (p = 0.007). The removal of C. albicans was also considerably affected by the denture base polymers and denture cleansers (p < 0.05). Lucitone®, Tokuyama®, and Kooliner® denture base polymers immersed for 3 min in eugenol showed the best results of removal. Discussion This study’s overall results showed that all denture polymers used as denture bases had an effect on C. albicans initial adherence and removal from the denture base, and eugenol is comparable to commercialised denture cleansers in reducing the number of attached C. albicans on denture base polymers.
Keywords: Candida albicans; Denture base polymers; eugenol; Denture cleansers; Fungal adherence